2007
DOI: 10.1002/ijc.23115
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous human papillomavirus 88: Remarkable differences in viral load

Abstract: A human papillomavirus (HPV) was cloned from a patient with multiple squamous cell carcinomas (SCCs) and identified as HPV88, recently categorized into a new species within the genus Gamma. The HPV88 viral load in an SCC of the index patient exceeded 1 million copies/cell. By contrast, a survey of 447 skin lesions (79 actinic keratoses, 73 seborrhoeic keratoses, 169 basal cell carcinomas and 126 SCCs) and 362 healthy skin biopsies found detectable HPV88 DNA in only 7 specimens. All these had very low viral loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…We found that SK lesions harboured higher amounts of virus than AK; however, due to the small number of observations, this finding requires further investigation. Also, when only minute amounts of virus are present, the possibility that results may reflect contamination rather than actual infection needs to be considered, in particular with regard to the remarkable viral loads of cutaneous HPV-88 described recently (Kullander et al, 2008). We found that many HPV-positive lesions contained higher amounts of virus on top of the lesion than in the lesion itself, in line with previous reports (Forslund et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…We found that SK lesions harboured higher amounts of virus than AK; however, due to the small number of observations, this finding requires further investigation. Also, when only minute amounts of virus are present, the possibility that results may reflect contamination rather than actual infection needs to be considered, in particular with regard to the remarkable viral loads of cutaneous HPV-88 described recently (Kullander et al, 2008). We found that many HPV-positive lesions contained higher amounts of virus on top of the lesion than in the lesion itself, in line with previous reports (Forslund et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Skin samples from SCC, AK, seborrhoeic keratosis (SK), and BCC commonly contain multiple HPV types, but typically at very low viral loads [4], [5], [7], [19], [30], [31]. Conventional methods for virus detection suffer from low throughput and are furthermore biased towards identifying sequences homologous to the PCR primers used.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional methods for virus detection suffer from low throughput and are furthermore biased towards identifying sequences homologous to the PCR primers used. There are several examples of NMSC lesions that contain very high amounts of previously uncharacterized HPV types that may escape detection by PCR systems based on known HPV sequences [7], [30]. This has made it difficult for epidemiologic studies to perform an unbiased assessment of which HPV types are present in healthy skin as compared to benign tumors or NMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…To preferentially amplify HPV, MDA with random and HPV-generic primers was done on 83 SCC biopsies (26). After digestion with 5 units HincII (New England Biolabs), the samples were run on a 1% agarose gel.…”
Section: Introductionmentioning
confidence: 99%